(untitled) (Jurnal Bahasa, 2019)
This paper aims to discuss the aspects of orthography and phonological representation, morphology and etymological informations of the ’A’ entry in Thomas Bowrey’s dictionary. Diachronic comparisons are the basis of this analysis. The review method was used in this study to scrutinize every headword in this entry. The ’A’ entry in this dictionary contains 164 words that consist of rootwords and polymorphic words. The deconstruction of the ’A’ entry includes comparisons with more modern dictionaries and other corpus data, such as Kamus Dewan Edisi Keempat (KD, 2007), A Malay-English Dictionary (Richard James Wilkinson, 1903), A Comprehensive Indonesian-English Dictionary (Stevens and Schmidgall-Tellings, 2010), Kamus Besar Bahasa Indonesia (online), Malay Concordance Project (online) and SEAlang Project (online), while other sources such as The Pigafetta Word List (1523) and de Houtmann (1598-1603) are used as tools to enhance the examination of Thomas Bowrey’s dictionary data and to represent contemporary data with it. This analysis not only focuses on the headwords but also takes into account the examples of phrases and clauses given by Bowrey, as well as the dialogues that accompany some words. The result of this analysis shows that the Malay language of 400 years ago was very close to the modern Malay language and was used in business, government affairs and socio-cultural aspects of the Malay community. Keywords: Diachronic comparison, historical-comparative comparison, Thomas Bowrey’s Dictionary